Onychopapillomas: a 68‐case series to determine best surgical procedure and histologic sectioning. (12th July 2018) - Delvaux, C.; Richert, B.; Lecerf, P.; André, J.
Abstract: Background: Onychopapilloma (OP) is a benign longitudinal nail bed tumour usually presenting as longitudinal erythronychia. Evidence‐based recommendations for proper histologic sectioning and definitive surgical management are not available. Objectives: The aim of this study was threefold. The first was to review the clinical and histopathological features of all OP diagnosed in our department. The second was to identify the most accurate histological technique. The third aim was to determine the most effective surgical procedures by examining recurrence rates and complications over the long term. Methods: This retrospective analysis collected all patients with OP in the dermatology department of Saint‐Pierre – Brugmann University Hospital (Brussels, Belgium) between January 2007 and March 2017. Clinical findings and type of surgery performed were recorded from medical files and iconographic documents. All slides were reviewed by a dermatopathologist with expertise in nail disease. Longitudinal follow‐up was performed. Results: A total of 68 patients were included (42 women, 26 men) with a median age of 46 years. Two children were 9 and 11. The histological interpretation was more difficult for the transverse sections than for the longitudinal ones (29.4% vs. 2.2%). The pathological diagnosis of OP was typical in 30.6%, suggestive in 51.6%, slightly suggestive in 12.9% and not contributive in 4.8%. 50 patients had a mean follow‐up of 50 months. 38% recovered completely and 20% recurred. 42% had mild to moderate sequelae. Conclusions: We report herein the first two paediatric cases. Classical longitudinal excision with careful removal of the lesion from the inferior face of the nail plate seems to be the most accurate surgical technique. In the pathology laboratory, longitudinal sections should be recommended. In our series, a recurrence rate of 20% was observed. This was more frequent when a tangential longitudinal excision was performed. Abstract : Linked article: This article is commented on by E. Haneke, pp. 1839–1840 in this issue. To view this articlehttps://doi.org/10.1111/jdv.14966